The effect of cup outer sizes on the contact mechanics and cement fixation of cemented total hip replacements. Issue 10 (October 2015) - Hua, Xijin; Li, Junyan; Wang, Ling; Wilcox, Ruth; Fisher, John; Jin, Zhongmin
Highlights Two cup designs with cup outer diameters of 40 and 43 mm were modelled. The differences of peak stresses in the acetabular cup between the two cup designs were negligible. The stresses of the cement mantle for cup design of 40 mm were higher than that of 43 mm. The differences of the stresses in the cement mantle between the two cup designs were compared to the clinical performance of the two cup designs.